Corporate Governance Attributes and CEO Turnover: Evidence from a Frontier Market - Lajmi, Azhaar; Dakhlaoui, Mejda; Flah, Ines Ben; Arfaoui, Khawla (International Review of Management and Marketing, 2025)
Based on managerial power and agency theories, this study aims to provide empirical evidence on corporate governance- chief executive officer (CEO) turnover relationship. Authors investigate a sample of 44 firms listed on the Tunis Stock Exchange (TSE) over the 2014-2019 period, using the logistic regression method. Results show that board size, its independence and its diligence have a significant and a positive effect on CEO turnover. Then, board independence is likely to be a key factor in the removal of an underperforming CEO. However, managerial ownership has a significant and a negative effect on CEO turnover. The findings regarding board size, board diligence, managerial ownership and CEO turnover are still valid when checking results robustness. The paper contributes to the corporate governance literature by focusing on corporate governance-CEO turnover on a frontier market. Empirical and practical contributions are present in our paper. Especially, this study provides policymakers and managers with insights into factors that influence CEO turnover in a frontier context such as Tunisia. Our findings also offer implications for corporations, investors, regulators, and academic researchers, by highlighting areas needing considerable attention pertaining to corporate governance. The paper contributes to the existing literature by focusing on the relationship corporate governance-CEO turnover on a frontier market. It provides further empirical support and enhances corporate governance practices.